2013
DOI: 10.1016/j.crme.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of local friction along a model pile shaft in a calibration chamber for a large number of loading cycles

Abstract: This Note presents the results of axial loading tests carried out on an instrumented "pileprobe" jacked into sand, in a calibration chamber, aimed at studying the evolution of local friction, up to very large numbers of cycles (10 5 cycles). After an initial phase of friction degradation (cyclic softening), a subsequent phase of mobilized friction reinforcement (cyclic hardening) is observed, which continues to develop up to very large numbers of cycles. The complete mechanism of shear degradation followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The vertical stress is applied to the specimen by applying a water pressure, p conf,v , through a large diameter bottom piston and the horizontal stress is applied, independently, through a water pressure, p conf,h , which horizontally confines the specimen contained in a neoprene membrane. For sand testing, a comprehensive description of the equipment and associated testing procedure has been given by Bekki et al (2013) and more details will be found in that paper.…”
Section: The Calibration Chamber Testing Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The vertical stress is applied to the specimen by applying a water pressure, p conf,v , through a large diameter bottom piston and the horizontal stress is applied, independently, through a water pressure, p conf,h , which horizontally confines the specimen contained in a neoprene membrane. For sand testing, a comprehensive description of the equipment and associated testing procedure has been given by Bekki et al (2013) and more details will be found in that paper.…”
Section: The Calibration Chamber Testing Setupmentioning
confidence: 99%
“…Different authors (Tali 2011;Bekki et al 2013;Muhammed 2015) have defined and used a coefficient of friction evolution C e,fs , as defined below, in order to easily quantify the evolution of local friction during cyclic loading and to make an easy distinction between degradation phases, corresponding to a decrease of C e,fs and reinforcement phases, corresponding to an increase of this coefficient, with respect to the initial mobilization of friction observed on the first cycle. In the present work, the coefficient of evolution has also been adopted in order to further analyse and quantify the evolution of local friction behaviour during the cyclic sequence.…”
Section: Analysis Of the Cyclic Sequencementioning
confidence: 99%
See 1 more Smart Citation
“…Grenoble Alpes interface were linked to shaft friction evolution during cycles. After a degradation phase observed by several authors, an increase in skin friction was measured by Bekki et al [4] for high number of cycles (between 100 and 100 000 cycles). These phenomena were attributed to the formation of a shear band of crushed grains around the shaft and a sand densification around the probe.…”
Section: Introductionmentioning
confidence: 83%
“…Le Kouby et al [9] and D' Aguiar et al [10] found that the bearing capacity of a pile would be significantly improved when the amplitude of any cyclic loading was optimised. Bekki et al [11] indicated that the side friction on a pile would show strain hardening because of the phenomenon of shear dilatancy under a large number of cycles. Chen et al [12] and Ren [13] studied the cyclic performance of pile foundation subjected to long-term axial cyclic loading in silt.…”
Section: Introductionmentioning
confidence: 99%